The satanic mechanic eaudiobook - Andrew, Sally (Tannie Maria Mystery., 2017)
Meet Tannie Maria - recipe writer turned crime fighter - and before she has time to take her Venus Chocolate Cake out of the oven, our glorious heroine finds herself embroiled in another mystery. In this wonderful sequel to Recipes for Love and Murder, Slimkat the bushman finds his life under threat and Tannie Maria is determined to find out who wants to kill him. But her new boyfriend, Detective Lieutenant Henk Kannemeyer, is keen to keep Tannie out of danger. And while new love is sweet, Tannie's pretty sure Henk's hiding something, so she has mysteries of her own solve. Blending a perfect whodunnit with lovable characters, Sally Andrew really does have the perfect recipe for a crime series.